Diseases of the Salivary Glands - Sisto, Margherita (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
A large number of diseases affect salivary gland (SG) secretion through different mechanisms, leading to SG dysfunction and associated oral problems. The glands may suffer from viral, bacterial, and, albeit rarely, fungal infections, which may cause painful swelling or obstruction; they could also become the target of an autoimmune attack or may be affected by various benign and malignant tumors which consist of a heterogeneous group of lesions with complex clinical-pathological characteristics. The loss of normal SG function results in widespread deterioration of oral health. This book, entitled "Diseases of Salivary Glands", provides an overview of recent advances in the field of SG disorders, focusing on the cellular and molecular mechanisms involved in the pathogenesis of SG diseases and on the most innovative investigation techniques that could help to preserve patients' health, function, and quality of life.